A biaxially stretched polypropylene film for capacitors and preparation method thereof

By mixing the cycloolefin copolymer with polypropylene and dispersing nanoporous silica in the polypropylene film, the polypropylene film for capacitors is prepared by biaxial tensile technology, which solves the problems of poor thermal stability and low mechanical strength of the polypropylene film at high temperatures, and achieves the high temperature resistance and mechanical properties of the polypropylene film.

CN118878881BActive Publication Date: 2025-03-18TONGLING HONGSHENG BAICHENG NEW ENERGY TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411065221.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2025-03-18
Estimated Expiration
2044-08-05

AI Technical Summary

Technical Problem

Polypropylene films have poor thermal stability and low mechanical strength at high temperatures, which limits their application in capacitors.

Method used

Polypropylene films for capacitors are prepared by mixing the cycloolefin copolymer with polypropylene and dispersing the nanoporous silica in it evenly.

Benefits of technology

It significantly improves the high temperature resistance and mechanical properties of polypropylene films, and improves its resistance to deformation and damage in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a biaxially stretched polypropylene film for capacitors and a preparation method thereof, comprising the following steps: step 1, uniformly mixing nanoporous silica and cycloolefin copolymer, extruding them twice through a double-screw extruder, melting them at high temperature, hot pressing them on a flat vulcanizer, and then granulating them to obtain a mixed cycloolefin copolymer; step 2, blending the mixed cycloolefin copolymer and polypropylene through a torque rheometer, casting them through a casting machine, and biaxially stretching them to obtain a polypropylene film; the biaxially stretched polypropylene film for capacitors prepared by the invention is prepared by mixing the cycloolefin copolymer and the polypropylene, and the heat resistance of the polypropylene film is improved; the high temperature resistance and mechanical properties of the polypropylene film are further improved by uniformly mixing the nanoporous silica in the cycloolefin copolymer; the nanoporous silica is uniformly dispersed in the polypropylene through the cycloolefin copolymer, and the prepared polypropylene film has excellent heat resistance and high mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic polymer processing, relates to a polypropylene film, and specifically relates to a biaxially stretched polypropylene film for capacitors and a preparation method thereof. Background Art

[0002] Polypropylene film capacitors are widely used due to their high power density and fast charge and discharge cycles. However, the low dielectric constant and limited discharge energy density of polypropylene film hinder the development of lightweight and integrated power modules. In addition, its low mechanical strength and poor thermal response limit its wide application. High thermal stability can avoid overheating caused by heat accumulation. The operating temperature of polypropylene film capacitors is low. Overheating will affect the performance of polypropylene film capacitors and significantly reduce the charge and discharge efficiency.

[0003] The main limitation of polypropylene film is that the maximum operating temperature is 105°C with appropriate voltage derating. Above this temperature, the polymer will lose its mechanical integrity at higher temperatures. The modification method of polypropylene film in the prior art is to add some other filling components or additives to polypropylene through mechanical blending to obtain high-performance polypropylene material. Blending is simple and easy with low cost. The commonly used filling components are nano-inorganic fillers. However, due to the poor compatibility of polar nano-inorganic fillers with non-polar polypropylene polymers, and the strong tendency of nano-inorganic fillers themselves to agglomerate, they are difficult to disperse in conventional blending methods and cannot improve the heat resistance and mechanical strength of polypropylene polymers.

[0004] Patent CN115195004A discloses a method for improving the high-temperature breakdown performance of capacitor polypropylene film based on γ-ray irradiation cross-linking modification. The method improves the insulation performance of the polypropylene film in a high-temperature environment by preparing a polypropylene mixture film with a sensitizer and polypropylene pellets and then irradiating it with a 60Co-γ-ray source. The heat resistance of the film capacitor is improved, but this solution has limited effect on improving the mechanical strength of the polypropylene film.

[0005] Patent CN102558775A discloses an ultra-thin polyester film for capacitors and a production method thereof. By adding nano-scale spherical silica and metal acetate compounds to the film material, the film has properties such as uniform thickness, excellent dielectric properties, and excellent thermal stability. This indicates that nano-silicon dioxide can improve the thermal stability of polymer films. Therefore, a biaxially stretched polypropylene film for capacitors and a preparation method thereof are needed, which utilizes nano-silicon dioxide to improve the thermal stability and mechanical strength of the polypropylene film. Summary of the invention

[0006] The object of the present invention is to provide a biaxially stretched polypropylene film for capacitors and a preparation method thereof, so as to solve the problems of poor thermal stability and low mechanical strength of the polypropylene film at high temperatures.

[0007] The invention mixes cycloolefin copolymer with polypropylene and mixes nanoporous silica with the cycloolefin copolymer, thereby improving the thermal stability and mechanical strength of the polypropylene film at high temperature through the synergistic effect of the nanoporous silica and the cycloolefin copolymer.

[0008] The purpose of the present invention can be achieved through the following technical solutions:

[0009] A method for preparing a biaxially stretched polypropylene film for capacitors comprises the following steps:

[0010] Step 1, mixing the nanoporous silica and the cycloolefin copolymer uniformly, pouring them into a double-screw extruder for extrusion to obtain a primary extrusion resin, pouring the primary extrusion resin and the cycloolefin copolymer into the double-screw extruder for extrusion again to obtain a secondary extrusion resin, melting the secondary extrusion resin at high temperature, hot pressing it on a flat vulcanizer to a thickness of 300-500 μm, then water cooling, air drying, granulating, and drying to obtain a mixed cycloolefin copolymer;

[0011] Step 2, blending the mixed cyclic olefin copolymer and polypropylene at 210-220° C. with a torque rheometer at a rotor speed of 50-60 rpm for 3-5 min, casting the mixture through a twin-screw extruder and a casting machine at 220-230° C. to obtain a cast sheet, and synchronously biaxially stretching the cast sheet through a double-stretching device to obtain a polypropylene film;

[0012] Nanoporous silica is prepared by the following steps:

[0013] The diblock copolymer is dissolved in a dilute hydrochloric acid solution with a pH value of 2-2.5, and a sodium hydroxide solution is added dropwise to the dilute hydrochloric acid solution until the pH value is 7-7.2 to obtain a copolymer solution. A carbon dioxide aqueous solution is added to the copolymer solution, and tetramethyl orthosilicate is added after stirring and mixing. The mixture is stirred at 60-70° C. for 20-30 minutes, and then the pH value is adjusted to 2-3 with dilute hydrochloric acid. The mixture is centrifuged, precipitated, washed, and dried to obtain nanoporous silica.

[0014] Furthermore, in step 1, the mass ratio of nanoporous silica to cycloolefin copolymer is 1-2:4-8, the mass ratio of primary extrusion resin to cycloolefin copolymer is 1-2:4-8; and in step 2, the mass ratio of mixed cycloolefin copolymer to polypropylene is 6-10:30-35.

[0015] Further, the diblock copolymer is prepared by the following steps:

[0016] Mix 2-(dimethylamino)ethyl methacrylate and anhydrous tetrahydrofuran in a flask, add 1-methoxy-1-(trimethylsilyloxy)-2-methyl-1-propylene, stir and react for 40-60 minutes, then add 2-(diisopropylamino)ethyl methacrylate dropwise into the flask, stir and react for 40-60 minutes, add methanol, remove the solvent by rotary evaporation, and vacuum dry at 50-60°C for 48-72 hours to obtain a diblock copolymer.

[0017] Furthermore, the volume ratio of ethyl 2-(dimethylamino)methacrylate, anhydrous tetrahydrofuran, 1-methoxy-1-(trimethylsilyloxy)-2-methyl-1-propylene, ethyl 2-(diisopropylamino)methacrylate and methanol is 2-3:20-30:0.1-0.2:7-8:0.4-1.

[0018] Further, the carbon dioxide aqueous solution is prepared by the following steps:

[0019] The adsorbent is mixed with deionized water of equal mass to obtain an adsorbent aqueous solution, and carbon dioxide is introduced into the adsorbent aqueous solution at 20-25° C. until the adsorbent aqueous solution reaches a constant weight to obtain a carbon dioxide aqueous solution.

[0020] Further, the adsorbent is prepared by the following steps:

[0021] Dissolve monoethanolamine in anhydrous ethanol in a flask, heat in a water bath to 25-30°C and stir magnetically, dissolve glycine in anhydrous ethanol and slowly add dropwise to the flask, react for 2-3 hours after the addition is complete, remove the anhydrous ethanol by vacuum evaporation, wash with anhydrous ethanol 2-3 times, and vacuum dry for 24-48 hours to obtain an adsorbent.

[0022] Furthermore, the usage ratio of monoethanolamine to anhydrous ethanol is 0.5-0.75 mol: 100-150 mL; the usage ratio of glycine to anhydrous ethanol is 0.5-0.75 mol: 100-150 mL.

[0023] Furthermore, the mass fraction of the diblock copolymer in the copolymer solution is 0.5-1.5wt%.

[0024] Beneficial effects of the present invention:

[0025] (1) The biaxially stretched polypropylene film for capacitors prepared by the present invention is prepared by mixing cycloolefin copolymer and polypropylene, which improves the heat resistance of the polypropylene film. By uniformly mixing nanoporous silica in the cycloolefin copolymer, the high temperature resistance and mechanical properties of the polypropylene film are further improved. The nanoporous silica is uniformly dispersed in the polypropylene through the cycloolefin copolymer and can be prepared into a capacitor film by biaxial stretching. The prepared polypropylene film has excellent heat resistance and high mechanical strength.

[0026] (2) The present invention mixes nanoporous silica with cycloolefin copolymer and extrude the mixture twice, so that the nanoporous silica is dispersed more evenly in the cycloolefin copolymer. The mixture is then hot-pressed in a flat-plate vulcanizer. Under the action of pressure, the pores of the nanoporous silica are filled with the cycloolefin copolymer, thereby reducing the agglomeration of the nanoporous silica and improving the compatibility of the nanoporous silica with polypropylene, thereby improving the mechanical properties and heat resistance of the polypropylene film.

[0027] (3) The present invention deposits nanoporous silica in a diblock copolymer by a template method, so that the obtained nanoporous silica has a small particle size and a stable morphology. By mixing a carbon dioxide aqueous solution with the diblock copolymer, the nanoporous silica is impacted by the carbon dioxide gas during deposition, thereby increasing the porosity of the nanoporous silica and helping to improve the compatibility of the nanoporous silica with polypropylene.

[0028] (4) The present invention uses monoethanolamine to prepare an adsorbent for adsorbing carbon dioxide. When depositing to form nanoporous silica, it not only has the function of releasing carbon dioxide, but also has the function of stabilizing the diblock copolymer, slowing down the deposition rate of the nanoporous silica, and helping to form a more stable nanoporous silica with more uniform pores. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Embodiment 1: A method for preparing a biaxially stretched polypropylene film for capacitors, comprising the following steps:

[0031] Step 1: Dissolve 0.5 mol monoethanolamine in 100 mL anhydrous ethanol in a flask, heat to 25°C in a water bath and stir magnetically, set a reflux condenser on top, dissolve 0.5 mol glycine in 100 mL anhydrous ethanol and slowly add it dropwise to the flask, react for 2 hours after the addition is complete, remove the anhydrous ethanol by vacuum evaporation, wash twice with anhydrous ethanol, and then vacuum dry for 24 hours to obtain an adsorbent.

[0032] Step 2: Mix the adsorbent with deionized water of equal mass to obtain an adsorbent aqueous solution, and introduce carbon dioxide into the adsorbent aqueous solution at 20° C. The introduction pressure of carbon dioxide is 0.1 MPa, and carbon dioxide is introduced until the adsorbent aqueous solution reaches a constant weight to obtain a carbon dioxide aqueous solution.

[0033] Step 3: Mix 10 mL of 2-(dimethylamino)ethyl methacrylate and 100 mL of anhydrous tetrahydrofuran in a flask, add 0.5 mL of 1-methoxy-1-(trimethylsilyloxy)-2-methyl-1-propylene, stir and react for 40 min, then add 35 mL of 2-(diisopropylamino)ethyl methacrylate dropwise into the flask at a rate of 1 mL / min, stir and react for 40 min, add 2 mL of methanol, remove the solvent by rotary evaporation, and dry under vacuum at 50 °C for 48 h to obtain a diblock copolymer.

[0034] Step 4, dissolving the diblock copolymer in a dilute hydrochloric acid solution with a pH value of 2, adding sodium hydroxide solution to the dilute hydrochloric acid solution until the pH value is 7 to obtain a copolymer solution, wherein the mass fraction of the diblock copolymer in the copolymer solution is 0.5wt%, adding 100mL of carbon dioxide aqueous solution to 100mL of the copolymer solution, stirring and mixing, adding 50mL of tetramethyl orthosilicate, stirring and reacting at 60°C for 20min, and then adjusting the pH to 2 with dilute hydrochloric acid, collecting the precipitate after centrifugation, washing twice with anhydrous ethanol and drying at 50°C to obtain nanoporous silica.

[0035] Step 5, 1g of nanoporous silica and 5g of cycloolefin copolymer are mixed evenly, poured into a twin-screw extruder for extrusion to obtain a primary extrusion resin, and then 1g of the primary extrusion resin and 5g of the cycloolefin copolymer are poured into the twin-screw extruder for extrusion again to obtain a secondary extrusion resin, and the secondary extrusion resin is melted at high temperature and hot-pressed on a flat vulcanizer to a thickness of 300μm, and then granulated and dried after water cooling and air drying to obtain a mixed cycloolefin copolymer.

[0036] Step six, 6g of mixed cycloolefin copolymer and 30g of polypropylene were blended at 210°C through a torque rheometer with a rotor speed of 50rpm for 3min, and cast through a twin-screw extruder and a casting machine at 220°C to obtain a cast sheet, and the cast sheet was synchronously biaxially stretched by a double-stretching device at a stretching temperature of 140°C, a stretching speed of 10% / s, and a biaxial stretching ratio of 7 times in the longitudinal direction and 8 times in the transverse direction to obtain a polypropylene film.

[0037] Embodiment 2: A method for preparing a biaxially stretched polypropylene film for capacitors, comprising the following steps:

[0038] Step 1: Dissolve 0.65 mol of monoethanolamine in 125 mL of anhydrous ethanol in a flask, heat to 27.5°C in a water bath and stir magnetically, set a reflux condenser on top, dissolve 0.65 mol of glycine in 125 mL of anhydrous ethanol and slowly add it dropwise to the flask, react for 2.5 hours after the addition is complete, remove the anhydrous ethanol by vacuum evaporation, wash twice with anhydrous ethanol, and then vacuum dry for 36 hours to obtain an adsorbent.

[0039] Step 2: Mix the adsorbent with deionized water of equal mass to obtain an adsorbent aqueous solution, and introduce carbon dioxide into the adsorbent aqueous solution at 22.5° C. The introduction pressure of carbon dioxide is 0.1 MPa, and carbon dioxide is introduced until the adsorbent aqueous solution reaches a constant weight to obtain a carbon dioxide aqueous solution.

[0040] Step 3: Mix 12.5 mL of 2-(dimethylamino)ethyl methacrylate and 125 mL of anhydrous tetrahydrofuran in a flask, add 0.75 mL of 1-methoxy-1-(trimethylsilyloxy)-2-methyl-1-propylene, stir and react for 50 min, then add 37.5 mL of 2-(diisopropylamino)ethyl methacrylate dropwise into the flask at a rate of 1 mL / min, stir and react for 50 min, add 3.5 mL of methanol, remove the solvent by rotary evaporation, and dry under vacuum at 55°C for 60 h to obtain a diblock copolymer.

[0041] Step 4, dissolving the diblock copolymer in a dilute hydrochloric acid solution with a pH value of 2.2, adding sodium hydroxide solution to the dilute hydrochloric acid solution until the pH value is 7.1 to obtain a copolymer solution, wherein the mass fraction of the diblock copolymer in the copolymer solution is 1wt%, adding 150mL of carbon dioxide aqueous solution to 125mL of the copolymer solution, stirring and mixing, adding 65mL of tetramethyl orthosilicate, stirring and reacting at 65°C for 25min, then adjusting the pH to 2.5 with dilute hydrochloric acid, collecting the precipitate after centrifugation, washing twice with anhydrous ethanol and drying at 55°C to obtain nanoporous silica.

[0042] Step 5, 1.5g of nanoporous silica and 6.5g of cycloolefin copolymer are mixed evenly, poured into a twin-screw extruder for extrusion to obtain a primary extrusion resin, and then 1.5g of the primary extrusion resin and 6.5g of the cycloolefin copolymer are poured into the twin-screw extruder for extrusion again to obtain a secondary extrusion resin, and the secondary extrusion resin is melted at high temperature and hot-pressed on a flat vulcanizer to a thickness of 400μm, and then granulated and dried after water cooling and air drying to obtain a mixed cycloolefin copolymer.

[0043] Step six, 8g of mixed cycloolefin copolymer and 32.5g of polypropylene were blended at 215°C through a torque rheometer with a rotor speed of 55rpm for 4min, and cast through a twin-screw extruder and a casting machine at 225°C to obtain a cast sheet, and the cast sheet was synchronously biaxially stretched by a double-stretching device at a stretching temperature of 145°C, a stretching speed of 10% / s, and a biaxial stretching ratio of 7 times in the longitudinal direction and 8 times in the transverse direction to obtain a polypropylene film.

[0044] Embodiment 3: A method for preparing a biaxially stretched polypropylene film for capacitors, comprising the following steps:

[0045] Step 1: Dissolve 0.75 mol of monoethanolamine in 150 mL of anhydrous ethanol in a flask, heat to 30°C in a water bath and stir magnetically, set a reflux condenser on top, dissolve 0.75 mol of glycine in 150 mL of anhydrous ethanol and slowly add it dropwise to the flask, react for 3 hours after the addition is complete, remove the anhydrous ethanol by vacuum evaporation, wash with anhydrous ethanol 3 times, and then vacuum dry for 48 hours to obtain an adsorbent.

[0046] Step 2: Mix the adsorbent with deionized water of equal mass to obtain an adsorbent aqueous solution, and introduce carbon dioxide into the adsorbent aqueous solution at 25° C. The introduction pressure of carbon dioxide is 0.1 MPa, and carbon dioxide is introduced until the adsorbent aqueous solution reaches a constant weight to obtain a carbon dioxide aqueous solution.

[0047] Step 3: Mix 15 mL of 2-(dimethylamino)ethyl methacrylate and 150 mL of anhydrous tetrahydrofuran in a flask, add 1 mL of 1-methoxy-1-(trimethylsilyloxy)-2-methyl-1-propylene, stir and react for 60 min, then add 40 mL of 2-(diisopropylamino)ethyl methacrylate dropwise into the flask at a rate of 1 mL / min, stir and react for 60 min, add 5 mL of methanol, remove the solvent by rotary evaporation, and dry under vacuum at 60 ° C for 72 h to obtain a diblock copolymer.

[0048] Step 4, dissolving the diblock copolymer in a dilute hydrochloric acid solution with a pH value of 2.5, adding sodium hydroxide solution to the dilute hydrochloric acid solution until the pH value is 7.2 to obtain a copolymer solution, wherein the mass fraction of the diblock copolymer in the copolymer solution is 1.5wt%, adding 200mL of carbon dioxide aqueous solution to 150mL of the copolymer solution, stirring and mixing, adding 75mL of tetramethyl orthosilicate, stirring and reacting at 70°C for 30min, and then adjusting the pH to 3 with dilute hydrochloric acid, collecting the precipitate after centrifugation, washing 3 times with anhydrous ethanol and drying at 60°C to obtain nanoporous silica.

[0049] Step 5, 2g of nanoporous silica and 8g of cycloolefin copolymer are mixed evenly, poured into a twin-screw extruder for extrusion to obtain a primary extrusion resin, and then 2g of the primary extrusion resin and 8g of the cycloolefin copolymer are poured into the twin-screw extruder for extrusion again to obtain a secondary extrusion resin, and the secondary extrusion resin is melted at high temperature and hot-pressed on a flat vulcanizer to a thickness of 500μm, and then granulated and dried after water cooling and air drying to obtain a mixed cycloolefin copolymer.

[0050] Step six, 10g of the mixed cycloolefin copolymer and 35g of polypropylene were blended at 220°C through a torque rheometer with a rotor speed of 60rpm for 5min, and cast through a twin-screw extruder and a casting machine at 230°C to obtain a cast sheet, and the cast sheet was synchronously biaxially stretched by a double-stretching device at a stretching temperature of 150°C, a stretching speed of 10% / s, and a biaxial stretching ratio of 7 times in the longitudinal direction and 8 times in the transverse direction to obtain a polypropylene film.

[0051] Principle of the invention:

[0052] The adsorbent is prepared from an ionic liquid synthesized by a hydroxylamino process based on acid-base neutralization of monoethanolamine and glycine. The adsorbent is filled with carbon dioxide due to the strong adsorption of the ionic liquid on carbon dioxide, and the obtained carbon dioxide aqueous solution has the function of releasing carbon dioxide gas; 2-(dimethylamino)ethyl methacrylate and 2-(diisopropylamino)ethyl methacrylate are polymerized into a diblock copolymer, and tetramethyl orthosilicate is deposited on the template of the diblock copolymer to form nano-silica; the carbon dioxide aqueous solution and the diblock copolymer are mixed in a partially neutral solution, so that the nano-silica deposited in the solution forms porous nano-silica under the action of carbon dioxide gas release; the monoethanolamine in the carbon dioxide aqueous solution has a stabilizing effect on the 2-(dimethylamino)ethyl methacrylate in the diblock copolymer, which can slow down the deposition rate of nanoporous silica, and at 60-70°C, the carbon dioxide has a stronger mobility, which helps to form a smaller volume and more pores. Nanoporous silica; after the deposition is completed, the block copolymer is deprotonated by adjusting the pH, so that it is dissolved in the solution, which is convenient for separating the nanoporous silica; the nanoporous silica is mixed with the cycloolefin copolymer and then subjected to secondary extrusion and hot pressing in a flat vulcanizer, so that the pores of the nanoporous silica are filled with the cycloolefin copolymer, the rigid cycloolefin copolymer improves the relaxation temperature and melting temperature of the polypropylene film, and can improve the heat resistance and mechanical properties of the polypropylene, and the cycloolefin polymer has good compatibility with the polypropylene, and the nano-silicon dioxide is uniformly dispersed in the polypropylene by utilizing the good compatibility of the cycloolefin copolymer with the polypropylene, the nano-scale pores and particle size in the nanoporous silica significantly enhance its surface energy and interface effect, which is helpful to form a more stable microstructure, improve the film's resistance to deformation and damage at high temperatures, reduce the thermal expansion coefficient of the material, and reduce the thermal stress caused by temperature changes, so that the polypropylene mixed resin is subjected to casting and biaxial stretching to obtain a polypropylene film with good heat resistance.

[0053] Comparative Example 1: The difference from Example 1 is that the preparation steps of nanoporous silica are:

[0054] The diblock copolymer was dissolved in a dilute hydrochloric acid solution with a pH value of 2, and a sodium hydroxide solution was added dropwise to the dilute hydrochloric acid solution until the pH value was 7 to obtain a copolymer solution, wherein the mass fraction of the diblock copolymer in the copolymer solution was 0.5wt%, 50mL of tetramethyl orthosilicate was added to 100mL of the copolymer solution, and carbon dioxide gas was continuously introduced into the solution at a pressure of 0.1Mpa. The reaction was stirred at 20°C for 20min, and then the pH was adjusted to 2 with dilute hydrochloric acid. The precipitate was collected after centrifugation, washed twice with anhydrous ethanol, and dried at 50°C to obtain nanoporous silica.

[0055] Comparative Example 2: The difference from Example 1 is that the preparation steps of nanoporous silica are:

[0056] The diblock copolymer was dissolved in a dilute hydrochloric acid solution with a pH value of 2, and a sodium hydroxide solution was added dropwise to the dilute hydrochloric acid solution until the pH value was 7 to obtain a copolymer solution, in which the mass fraction of the diblock copolymer in the copolymer solution was 0.5wt%. 50mL of tetramethyl orthosilicate was added to 100mL of the copolymer solution, and the mixture was stirred and reacted at 20°C for 20min, and then the pH was adjusted to 2 with dilute hydrochloric acid. After centrifugation, the precipitate was collected, washed twice with anhydrous ethanol, and dried at 50°C to obtain nanoporous silica.

[0057] Comparative Example 3: The difference from Example 1 is that the preparation steps of the mixed cycloolefin copolymer are:

[0058] 1 g of nanoporous silica and 10 g of cycloolefin copolymer were uniformly mixed, poured into a twin-screw extruder, and then granulated and dried after water cooling and air drying to obtain a mixed cycloolefin copolymer.

[0059] Comparative Example 4: Polypropylene film without mixed cyclic olefin copolymer.

[0060] The sources of some reagents in the embodiments and comparative examples are as follows:

[0061] Monoethanolamine, tetramethyl orthosilicate, 2-(diisopropylamino)ethyl methacrylate, and 2-(dimethylamino)ethyl methacrylate were purchased from Sigma-Aldrich.

[0062] Glycine was purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd.

[0063] Tetrahydrofuran was purchased from Shanghai MacLean Reagent Co., Ltd.

[0064] 1-Methoxy-1-(trimethylsilyloxy)-2-methyl-1-propene was purchased from Hubei Jusheng Technology Co., Ltd.

[0065] Polypropylene was Nordic film-grade polypropylene purchased from Dongguan Yufeng Plastic Chemical Co., Ltd.

[0066] Cyclic olefin copolymer is German TOPAS brand resin purchased from Guangzhou Jiushun New Materials Co., Ltd.

[0067] The polypropylene films prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to performance tests, mechanical properties were tested according to GB / T 16958-2008, thermal shrinkage was tested according to GB / T 18350-2018, and dielectric properties were tested according to GB / T 13542.2-2009. The results are shown in Table 1:

[0068] Table 1

[0069]

[0070] As can be seen from Table 1, the polypropylene films prepared in Examples 1 to 3 of the present invention have high tensile strength and good mechanical properties. Compared with ordinary polypropylene films, the tensile strength is improved to 270 MPa. In Comparative Example 1, carbon dioxide is directly introduced during the deposition of nano-silicon dioxide, resulting in large bubbles and high chaos in the solution, which leads to uneven deposition of nano-silicon dioxide and high agglomeration. The subsequent dispersion with the cycloolefin copolymer is poor, so the tensile strength of the polypropylene film is slightly improved. In Comparative Example 2, no carbon dioxide aqueous solution is added during the deposition of nano-silicon dioxide, and no single Due to the stabilizing effect of ethanolamine, the nano-silica deposition particle size is uneven and the porosity is low. The dispersion is reduced when preparing the mixed cycloolefin copolymer, resulting in a reduction in the dispersion in the polypropylene film. Therefore, the tensile strength of the polypropylene film is lower than that of Examples 1 to 3. In Comparative Example 3, since the nanoporous silica and the cycloolefin copolymer are not blended twice when mixed, the dispersion of the nanoporous silica is not high, and the nanoporous silica is not hot-pressed in a flat-plate vulcanizer, the compatibility of the nanoporous silica is reduced when the mixed cycloolefin copolymer is mixed with the polypropylene film, resulting in a tensile strength lower than that of Examples 1 to 3.

[0071] It can be seen from the heat shrinkage in Table 1 that the heat shrinkage of Examples 1 to 3 prepared by the present invention is all lower than 1%, indicating that the nanoporous silica dispersion of the polypropylene film prepared by the present invention is good, which improves the high temperature resistance of the polypropylene film and can maintain good mechanical properties and dielectric properties in a high temperature environment; Comparative Example 1 has a relatively poor dispersion of nano-silica, and the improvement of the high temperature resistance of the polypropylene film is relatively small; Comparative Example 2 has a lower heat shrinkage than Examples 1 to 3 due to the reduced porosity and the reduced degree of crosslinking with the cycloolefin copolymer; Comparative Example 3 has a higher heat shrinkage than Examples 1 to 3 due to the low degree of mixing of the nanoporous silica and the cycloolefin copolymer.

[0072] The dielectric constants of Examples 1 to 3 prepared by the present invention are high. Comparative Example 1 has a lower dielectric constant due to the uneven particle size of the nano-silica and the agglomeration phenomenon; Comparative Example 2 has fewer pores and larger particle size of the nanoporous silica, resulting in a lower dielectric constant of the polypropylene film than Examples 1 to 3; Comparative Example 3 has a smaller increase in the dielectric constant due to the uneven dispersion of the nanoporous silica.

[0073] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0074] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a biaxially stretched polypropylene film for capacitors, characterized in that: The steps include: Step 1, mixing the nanoporous silica and the cycloolefin copolymer uniformly, pouring them into a double-screw extruder for extrusion to obtain a primary extrusion resin, pouring the primary extrusion resin and the cycloolefin copolymer into the double-screw extruder for extrusion again to obtain a secondary extrusion resin, melting the secondary extrusion resin at high temperature, hot pressing it on a flat vulcanizer to a thickness of 300-500 μm, then water cooling, air drying, granulating, and drying to obtain a mixed cycloolefin copolymer; Step 2, blending the mixed cyclic olefin copolymer and polypropylene at 210-220° C. with a torque rheometer at a rotor speed of 50-60 rpm for 3-5 min, casting the mixture through a twin-screw extruder and a casting machine at 220-230° C. to obtain a cast sheet, and synchronously biaxially stretching the cast sheet through a double-stretching device to obtain a polypropylene film; The nanoporous silica is prepared by the following steps: The diblock copolymer is dissolved in a dilute hydrochloric acid solution with a pH value of 2-2.5, and a sodium hydroxide solution is added dropwise to the dilute hydrochloric acid solution until the pH value is 7-7.2 to obtain a copolymer solution, and a carbon dioxide aqueous solution is added to the copolymer solution, and tetramethyl orthosilicate is added after stirring and mixing, and the mixture is stirred at 60-70° C. for 20-30 minutes, and then the pH value is adjusted to 2-3 with dilute hydrochloric acid, and the mixture is centrifuged, washed, and dried to obtain nanoporous silica; The carbon dioxide aqueous solution is prepared by the following steps: The adsorbent is mixed with deionized water of equal mass to obtain an adsorbent aqueous solution, and carbon dioxide is introduced into the adsorbent aqueous solution at 20-25° C. until the adsorbent aqueous solution reaches a constant weight to obtain a carbon dioxide aqueous solution; The adsorbent is prepared by the following steps: Dissolve monoethanolamine in anhydrous ethanol in a flask, heat in a water bath to 25-30°C and stir magnetically, dissolve glycine in anhydrous ethanol and slowly add it dropwise to the flask, react for 2-3 hours after the addition is complete, remove the anhydrous ethanol by vacuum evaporation, wash with anhydrous ethanol 2-3 times, and then vacuum dry for 24-48 hours to obtain an adsorbent; The diblock copolymer is prepared by the following steps: Mix 2-(dimethylamino)ethyl methacrylate and anhydrous tetrahydrofuran in a flask, add 1-methoxy-1-(trimethylsilyloxy)-2-methyl-1-propylene, stir and react for 40-60 minutes, then add 2-(diisopropylamino)ethyl methacrylate dropwise into the flask, stir and react for 40-60 minutes, add methanol, remove the solvent by rotary evaporation, and vacuum dry at 50-60°C for 48-72 hours to obtain a diblock copolymer.

2. The method for preparing a biaxially stretched polypropylene film for capacitors according to claim 1, characterized in that: The mass ratio of the nanoporous silica to the cycloolefin copolymer in step 1 is 1-2:4-8, and the mass ratio of the once extruded resin to the cycloolefin copolymer is 1-2:4-8; the mass ratio of the mixed cycloolefin copolymer to polypropylene in step 2 is 6-10:30-35.

3. The method for preparing a biaxially stretched polypropylene film for capacitors according to claim 1, characterized in that: The volume ratio of 2-(dimethylamino)ethyl methacrylate, anhydrous tetrahydrofuran, 1-methoxy-1-(trimethylsilyloxy)-2-methyl-1-propylene, 2-(diisopropylamino)ethyl methacrylate and methanol is 2-3:20-30:0.1-0.2:7-8:0.4-1.

4. The method for preparing a biaxially stretched polypropylene film for capacitors according to claim 1, characterized in that: The usage ratio of monoethanolamine to anhydrous ethanol is 0.5-0.75 mol: 100-150 mL; the usage ratio of glycine to anhydrous ethanol is 0.5-0.75 mol: 100-150 mL.

5. The method for preparing a biaxially stretched polypropylene film for capacitors according to claim 1, characterized in that: The mass fraction of the diblock copolymer in the copolymer solution is 0.5-1.5 wt %.

6. A biaxially stretched polypropylene film for capacitors, characterized in that: Prepared by the preparation method described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Ultra-thin type polyester film for capacitor and production method thereof

    CN102558775A

  • Method for improving high-temperature breakdown performance of capacitor polypropylene film based on gamma-ray irradiation crosslinking modification

    CN115195004A

  • Biaxially oriented polypropylene film

    CN106029754A

  • Green preparation method of hollow mesoporous silica nanosphere

    CN107082432A

  • Biaxially oriented polypropylene film

    CN118414247A